Memaksimalkan Potensi Crm: Panduan Praktis Untuk Meningkatkan Kinerja Bisnis - Riha Fitria Ardelia; Adelia Eka Putri; Shivva Amalia Khoiralla; I.G.N. Andhika Mahendra (Jurnal Manajemen Bisnis Digital Terkini, 2024)
In an increasingly competitive business environment, Customer Relationship Management (CRM) is a strategic key for companies in maintaining customer satisfaction and improving performance. This article aims to investigate the influence of CRM on customer satisfaction and company performance to improve business performance. A qualitative approach is used to explore the complex interactions between Customer Relationship Management, customer satisfaction, and company performance from an in-depth perspective. Meanwhile, the literature study method is used to analyze various theories, models and related research findings. This research aims to evaluate the impact of Customer Relationship Management on customer satisfaction and company performance, providing a better understanding of how effective implementation of Customer Relationship Management can strengthen long-term relationships with customers and improve a company's overall business performance.